Empowering Women by Education about Toddler’s Nutrition in Posyandu Puspa Indah Nabire - Shanty Natalia; Ngatiyem; Sara Erari; Iace Douw; Paula Pekei; Maria Dior Pardede; Ernawati; Dandrika Mote; Gelara Nawipa; Serpina Bunai; Dela Tatogo (Universitas STRADA Indonesia, 2024)
Nutrition problems in developing countries, including Indonesia, show an increasing trend, one of which is the problem of stunting. Stunting is a nutritional problem caused by a long-term lack of nutritional intake during the first 1000 days of life, which is a critical period. Resulting in growth disorders in children. The high incidence of stunting is a concern for the government. Some of the causes of stunting itself are a lack of intake that is absorbed by the body from the time it is in the womb until after birth, lack of access to health services, lack of access to clean water and sanitation. Therefore, efforts need to be made to prevent stunting by improving diet and parenting patterns and sanitation. The aim of this community service is to increase mothers' knowledge about the importance of providing balanced nutritional and food intake for their children to prevent stunting. This activity is carried out by providing education with leaflets to mothers of toddlers about Balanced Nutrition. This counseling was carried out at Posyandu Puspa Indah, Nabire Regency. Which was attended by 13 mothers. The results of the counseling showed that mothers of toddlers understood the material provided. It is hoped that further counseling will focus on the growth and development of babies and toddlers.